2015
DOI: 10.3917/spub.153.0331
|View full text |Cite
|
Sign up to set email alerts
|

Ce que l’intervention fait à la recherche dans un contexte de maladie grave

Abstract: By placing in perspective two ongoing studies based on interventional research dynamics in the field of cancer, this article proposes a review of the specific effects of this type of research. Although this approach is often poorly regarded in the field of academic sociology, it is particularly adapted to the analysis of ongoing processes, providing access to certain phenomena that would be otherwise impossible to observe. The research worker's active involvement, the experience that he/she shares with the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…Learning that one has a serious illness is first of all an "event that's difficult to digest," a "shock" that may be a "source of unproductive violence, received as a blow, or even generate nothing less than a trauma" (STAVO-DEBAUGE, 2012, p. 191). Research-action studies on legal access in cases of serious pathologies have shown how the news of the illness can be a "staggering factor" for victims and their friends and families (MARCHAND, ROLLIN, 2015). Moving on from this state of immobility, 11.…”
Section: Family Reconfiguration When Confronting Illnessmentioning
confidence: 99%
“…Learning that one has a serious illness is first of all an "event that's difficult to digest," a "shock" that may be a "source of unproductive violence, received as a blow, or even generate nothing less than a trauma" (STAVO-DEBAUGE, 2012, p. 191). Research-action studies on legal access in cases of serious pathologies have shown how the news of the illness can be a "staggering factor" for victims and their friends and families (MARCHAND, ROLLIN, 2015). Moving on from this state of immobility, 11.…”
Section: Family Reconfiguration When Confronting Illnessmentioning
confidence: 99%
“…Marchand A., Rollin Z. (2015), « Ce que l'intervention fait à la recherche dans un contexte de maladie grave », Santé Publique, n°3, vol.…”
unclassified